Development of a Local Wisdom–Based Digital Comic Media Integrating the Sidakarya Mask to Enhance Cultural Literacy and Reading Outcomes in Primary Education - Yantika, I Wayan Ade; Putrayasa, Ida Bagus; Sudiana, I Nyoman (Jurnal Paedagogy, 2026)
This study aims to develop and examine the validity, practicality, and effectiveness of a digital comic learning media incorporating the local wisdom of the Sidakarya Mask to improve cultural literacy and reading learning outcomes among fifth-grade elementary school students. The study employed a Research and Development (R&D) method using the ADDIE model. The participants consisted of all fifth-grade students at SD Negeri 4 Peliatan, selected through total sampling. The effectiveness of the media was evaluated using a one-group pretest–posttest design. Data were collected through expert validation, teacher and student response questionnaires, and tests of cultural literacy and reading achievement. Data analysis involved qualitative and quantitative descriptive analysis, paired-sample t-tests, and N-Gain calculations. The results indicate that the developed media demonstrates very high validity and practicality. Its use significantly improved students’ cultural literacy and reading learning outcomes, as reflected by N-Gain scores of 0.58 for cultural literacy (moderate category) and 0.72 for reading learning outcomes (high category). In conclusion, the digital comic media incorporating the local wisdom of the Sidakarya Mask is feasible and effective for Bahasa Indonesia learning in elementary schools.